Global cardiovascular and renal outcomes of reduced GFR - Thomas, B; Matsushita, K; Abate, K; Jha, V (American Society of Nephrology, 2017)
The burden of premature death and health loss from ESRD is well described. Less is known regarding the burden of cardiovascular disease attributable to reduced GFR. We estimated the prevalence of reduced GFR categories 3, 4, and 5 (not on RRT) for 188 countries at six time points from 1990 to 2013. Relative risks of cardiovascular outcomes by three categories of reduced GFR were calculated by pooled random effects meta-analysis. Results are presented as deaths for outcomes of cardiovascular disease and ESRD and as disability-adjusted life years for outcomes of cardiovascular disease, GFR categories 3, 4, and 5, and ESRD. In 2013, reduced GFR was associated with 4% of deaths worldwide, or 2.2 million deaths (95% uncertainty interval [95% UI], 2.0 to 2.4 million). More than half of these attributable deaths were cardiovascular deaths (1.2 million; 95% UI, 1.1 to 1.4 million), whereas 0.96 million (95% UI, 0.81 to 1.0 million) were ESRD-related deaths. Compared with metabolic risk factors, reduced GFR ranked below high systolic BP, high body mass index, and high fasting plasma glucose, and similarly with high total cholesterol as a risk factor for disability-adjusted life years in both developed and developing world regions. In conclusion, by 2013, cardiovascular deaths attributed to reduced GFR outnumbered ESRD deaths throughout the world. Studies are needed to evaluate the benefit of early detection of CKD and treatment to decrease these deaths.